Anatomy of the proximal septal vein in patients with focal intramural ventricular arrhythmias. (16th March 2022) - Tam, Tsz‐kin; Liang, Jackson J.; Ghannam, Michael; Latchamsetty, Rakesh; Cochet, Hubert; Patel, Smita; Jongnarangsin, Krit; Morady, Fred; Bogun, Frank
Abstract: Background: Focal ventricular arrhythmias (VAs) originating from the intramural myocardium of the basal septum are difficult to localize and ablate. Proximal septal veins emptying into the great cardiac vein can reach close to the origin of intramural arrhythmias. Objective: To assess characteristics of proximal septal coronary veins in patients with intramural VAs. Methods and Results: Among 84 consecutive patients with intramural VAs, 29 patients (age 60 ± 11years, 16 males, ejection fraction 47 ± 13%) underwent preprocedural cardiac computed tomographic angiography (CTA). In 14 of these patients, the intramural site of origin (SOO) was identified with multipolar catheters. The intramural SOO could not be accessed with mapping catheters in the other 15 patients while mapping the coronary venous system. The CTA identified sizable proximal septal veins in all patients in whom the SOO could be accessed with mapping catheters. In the patients in whom the intramural SOO was not identified, the proximal septal veins were often either small (<2 mm at the branching site) or non‐existent ( n = 9, p = .001). The proximal septal veins in patients in whom the SOO was identified were larger than in the patients in whom the SOO could not be identified (3.0 ± 0.6 mm vs. 2.1 ± 0.9 mm, p = .01). Conclusions: Preprocedural imaging with CTAs can be beneficial in identifying the anatomy of proximal septal coronary veins that allow adequate mapping of patients with suspected intramural VAs.